Central-local financial relations in South Africa - Cameron, Robert (2002)
This article analyses central-local financial relations in South Africa. The first part develops a framework for decentralisation. The article then traces the history of local government finance during the apartheid era. There are two broad views on how to finance local government in South Africa. One is that it should primarily be self-financing; the alternative viewpoint is that local government should receive a substantially increased portion of the tax revenue. The article concludes that despite the greater constitutional status of local government, the Department of Finance's historically centralist view towards local government persists, and local government finance, and with it local government autonomy, is being centralised slowly. - Reproduced.
Keywords: Local government - South Africa; Local government